Correlation of Clinical Factors and Loss of Taste and Smell in Patients with Coronavirus Disease 2019 - Seyed Resuli, Ali; Öktem, Fatih (ENT Updates, 2021)
Objective: The Covid-19 pandemic continues to threaten the whole world. Early diagnosis of patients is very important to prevent the spread of the virus. Sudden loss of taste and smell is a common early symptom in patients. Therefore, it is thought that revealing the pathogenesis of the symptom will help both in early diagnosis and in predicting the prognosis. Materials and Methods: The age, gender, predominant symptoms during Covid, length of stay at home/hospital, and smoking status of patients who had Covid and had loss of taste and smell between July 2020 and December 2020 were evaluated retrospectively. Results: Patients with loss of taste and smell were significantly younger than those who did not. The majority were female patients, non-smokers, and patients needing significantly less hospitalization and receiving treatment at home. Among the accompanying symptoms, GIS symptoms were also significantly more common in this group. Conclusion: Loss of taste and smell is an important symptom in Covid-19 infection. Revealing the demographic and clinical characteristics associated with this symptom is valuable in terms of early diagnosis of the disease, predicting the prognosis and reducing the contagiousness.